Photoimmunotherapy for cancer-associated fibroblasts targeting fibroblast activation protein in human esophageal squamous cell carcinoma. Issue 9 (2nd September 2019) - Watanabe, Shinichiro; Noma, Kazuhiro; Ohara, Toshiaki; Kashima, Hajime; Sato, Hiroaki; Kato, Takuya; Urano, Shinichi; Katsube, Ryoichi; Hashimoto, Yuuri; Tazawa, Hiroshi; Kagawa, Shunsuke; Shirakawa, Yasuhiro; et al.
ABSTRACT: Cancer-associated fibroblasts (CAFs) are strongly implicated in tumor progression, including in the processes of tumorigenesis, invasion, and metastasis. The targeting of CAFs using various therapeutic approaches is a novel treatment strategy; however, the efficacy of such therapies remains limited. Recently, near-infrared photoimmunotherapy (NIR-PIT), which is a novel targeted therapy employing a cell-specific mAb conjugated to a photosensitizer, has been introduced as a new type of phototherapy. In this study, we have developed a novel NIR-PIT technique to target CAFs, by focusing on fibroblast activation protein (FAP), and we evaluate the treatment efficacy in vitro and in vivo . Esophageal carcinoma cells exhibited enhanced activation of fibroblasts, with FAP over-expressed in the cytoplasm and on the cell surface. FAP-IR700-mediated PIT showed induced rapid cell death specifically for those cells in vitro and in vivo, without adverse effects. This novel therapy for CAFs, designed as local control phototherapy, was safe and showed a promising inhibitory effect on FAP + CAFs. PIT targeting CAFs via the specific marker FAP may be a therapeutic option for CAFs in the tumor microenvironment in the future.